Design & Simulation of Dielectric Resonator Antenna for Millimeter Applications (International Journal of Scientific Research and Management (IJSRM), 2016)
This paper presents the design and simulation of broadband Dielectric Resonator antenna using HighFrequency Structure Simulator (HFSS). This paper investigate stacked cylindrical DRA,s placed on concentricannular rings .These hybrid nature of structure is operating under controlled electric fields and magneticfields. Higher gain has been reported in proposed work when electric bias is given , under magnetic biasbandwidth of the antenna is enhanced by making little bit compromise on the Gain. Frequency shift has also been notice during magnetic and electric bias condition .This can be wisely used for getting reconfigurability.